PENGARUH NUMBERED HEAD TOGETHER TERHADAP PEROLEHAN BELAJAR PENDIDIKAN KEWARGANEGARAAN PESERTA DIDIK DI SEKOLAH DASAR - Indrayuni, Desika; Marzuki, Marzuki; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to analyze the effect of the use of Numbered Head Together on the acquisition of learning of Citizenship Education of third grade students of State Elementary School 15 South Pontianak. The research method used is an experimental method. The form of the research is Quasi Experimental Design with the Time Series Design experimental design. The population and sample are class III students totaling 20 people. Based on data analysis, the average pre-test results were 49.50 and the average post-test results of students were 60.50. After the t test is obtained, tcount is 3.74, while the table with db = 20-1 = 19 and the significant level (α) = 5% is 1.729, it turns out thitung≥table or 3.74 ≥ 1.729, then Ha is accepted. This is the effect of using Numbered Head Together on the acquisition of Class III Student Citizenship Education learning. From the calculation of effect size (   ) obtained ES of 0.75 (medium criteria). This means that the use of Numbered Head Together has a moderate influence on the acquisition of learning for Citizenship Education of third grade students of SD Negeri 15 Pontianak Selatan. Keywords: Influence, Numbered Head Together, Learning Outcomes , Civic Education